CSR project with industry, students and community: cleaning and refurbishing the Kelanang Beach - Tengku Shamsudden, Tengku Azeezeen; Nordin, Nor Aizatul Syima; Samud, Nurul Nadia; Muniam, Roshini; Sallahuddin, Muhammad Akram; Ghani, Raziq (Universiti Teknologi MARA, Kedah, 2024)
The CSR initiative "Clean Beautiful Beach, Great Community!" was organized by the Social Club of the Academy of Language Studies, UiTM Shah Alam, in collaboration with Grundfos Pumps Sdn Bhd, and the Kuala Langat Municipal Council (MPKL). It was scheduled for June 21, 2024, at Kelanang Beach in Kuala Langat. The project aimed to clean the beach of harmful pollutants, restore facilities, and enhance community awareness about environmental conservation. The initiative also sought to engage university students and staff in practical environmental education, promoting a sustainable and cleaner beach environment. The project involved cleaning, mural painting and facility restoration to make the beach more attractive. The collaboration aimed to foster environmental responsibility among participants, preserve the local natural heritage, and boost community and tourist engagement, ultimately contributing to the local economy. A 10-point survey was conducted after the program ended to all the participants involved. The program's success hinges on the Sustainable Development Goals (SDG) 3 to promote a healthy life, SDG 4 in lifelong learning for students and the community on how to manage the cleanliness of not only the beach but all aspects of their lives. It is hoped that this program will be a sustained effort to ensure that the aims and objectives are fulfilled by future groups of students. This will lead to a better and cleaner environment for all.